Tolerar y reglamentar. La mala vida y la condición femenina en Pamplona al final del siglo XIX - Campo Guinea, María del Juncal (Huarte de San Juan. Geografía e Historia, 1998)
Prostitution, as women's activity associated to their sexual role, should be studied as part of an historican reality immersed in contradictions, ambiguoties and conjunctures of complex analysis. In the nineteenth century, the official concern about prostitution as dangerous form of sexual activity, whose limits were defined and controled by the state, leaded to the approval of several laws in most european countries. In Pamplona, Special Hygiene Rules were elaborated by the Tow Hall in 1889. Through them, it is possible to know how the town authorities faced such behaviour and what was their attitude in relation to the problem hence derived.
Keywords: Prostitution; special hygiene rules